PENGARUH NILAI KEKASARAN PERMUKAAN AGREGAT KASAR TERHADAP KUAT TEKAN BETON - Mawardi Mawardi; Besperi Besperi (Universitas Bengkulu, 2019)
The aim of this research was to find out the influence of surface cruduity value of coarse aggregater to pressure strength of concrete. The water ratio that aplicated was 0,5. The percentation of surface cruduity value were 100%, 50%, and 0% of the specimen. 9 cylinders of 150 x 300 mm specimens had been tested. It was showed the surface cruduity value to the concrete cause the strengths gettinglower as the percentation getting smaller (average 12 %).